Comparison of Psychological Readiness to Return to Sport After Primary Versus Revision Anterior Cruciate Ligament Reconstruction. Issue 5 (2nd May 2023) - Duncan, Brian R.; Reid, Matthew; Kleihege, Jacquelyn; Higbie, Steven; Gardner, Emily P.; Lowe, Walter; Bailey, Lane
Background: Rates of return to preinjury level of play after anterior cruciate ligament (ACL) reconstruction (ACLR) remain unsatisfactory, particularly for patients who undergo revision surgery. Psychological readiness is associated with successful return to sport (RTS) and self-perceived preinjury sport performance. Purpose: To compare psychological readiness at RTS between patients who underwent revision ACL autograft reconstruction and matched controls who underwent primary ACL autograft reconstruction. Study Design: Cohort study; Level of evidence, 3. Methods: Data were gathered using a single orthopaedic surgeon database of patients who underwent ACLR between 2015 and 2018. Patients who underwent revision ACLR and met the study criteria (N = 92) were matched by age, sex, graft type, and rehabilitation protocol to a control group of patients who underwent primary ACLR (n = 92). Functional assessment at release to play was examined using passive knee range of motion, single-leg squat, and single-leg hop testing. Self-reported outcomes included the International Knee Documentation Committee subjective function survey and the ACL–Return to Sport after Injury (ACL-RSI) psychological readiness scale. Time to release to play was recorded as the number of months needed to reach a ≥90% limb symmetry index from the date of the index ACLR. Data were assessed for normality using the Shapiro-Wilk test, and univariate general linear models were utilized with an alpha level of .05. Results: The overall mean patient age was 29.9 ± 10 years, and 40% of patients were women. No significant differences between groups were noted in any of the baseline patient characteristics or surgical findings. At RTS, the mean ACL-RSI score was significantly lower in the revision surgery group (77.4 ± 19.4 vs 85.3 ± 17.4; P = .011). In addition, the revision surgery group returned to play significantly later than the primary surgery group (9.4 ± 2 vs 8.1 ± 1.3 months, respectively; P < .001). Conclusion: When compared with primary ACL autograft reconstruction, revision reconstruction patients exhibited lower psychological readiness scores and a longer time to meet the objective criteria for RTS. Registration: NCT03704376 (ClinicalTrials.gov identifier).